Study of relation of Customer Psychology on their Buying Behaviour Towards FMCGs (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study aims to investigate the impact of customer psychology on their buying behavior towards fast-moving consumer goods (FMCGs). FMCGs are an essential part of consumers' daily lives, and understanding the factors that influence their buying decisions can help marketers develop effective marketing strategies. The study reviews the existing literature on customer psychology and buying behavior towards FMCGs and identifies several key psychological factors that influence consumer behavior, such as credibility, hedonic &pleasure, and attitudes. The research has used a descriptive study, to collect data from a 750 sample of FMCG consumers from Indore, Bhopal, Delhi, Pune, Bangalore across India. The results of the study provide insights into the relationship between customer psychology and buying behavior towards FMCGs and suggest practical implications for marketers to develop effective marketing strategies to target FMCG consumers.